2018
DOI: 10.1002/jat.3664
|View full text |Cite
|
Sign up to set email alerts
|

Glabridin attenuates antiadipogenic activity induced by 2,3,7,8‐tetrachlorodibenzo‐p‐dioxin in murine 3T3‐L1 adipocytes

Abstract: 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) has various toxicological effects in adipose tissue. Evidence is accumulating that glabridin, a flavonoid extracted from licorice, has beneficial effects on the regulation of glucose homeostasis. In this study, we investigated whether glabridin suppresses TCDD-induced loss of adipogenic action using 3T3-L1 adipocytes as a cell culture model of wasting syndrome. Glabridin effectively suppressed TCDD-induced loss of lipid accumulation in this model. Pretreating cells wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 66 publications
(76 reference statements)
0
9
0
Order By: Relevance
“…In addition, the inhibitory effect of TCDD on adipogenesis in C3H10T1/2 cells was shown to be aggravated by the epidermal growth factor (EGF) and the fibroblast growth factor (FGF) that were shown to potentiate AhR activation and the subsequent down-regulation of PPARγ expression [140]. Inhibition of PPARγ by dioxin may be at least partially mediated by the down-regulation of PPARγ coactivator 1 alpha production in murine 3T3-L1 adipocytes [141]. ERK activation was also considered as the potential mechanism of the inhibitory effect of TCDD on PPARγ1 expression in C3H10T1/2 cells [142].…”
Section: Dioxinmentioning
confidence: 99%
“…In addition, the inhibitory effect of TCDD on adipogenesis in C3H10T1/2 cells was shown to be aggravated by the epidermal growth factor (EGF) and the fibroblast growth factor (FGF) that were shown to potentiate AhR activation and the subsequent down-regulation of PPARγ expression [140]. Inhibition of PPARγ by dioxin may be at least partially mediated by the down-regulation of PPARγ coactivator 1 alpha production in murine 3T3-L1 adipocytes [141]. ERK activation was also considered as the potential mechanism of the inhibitory effect of TCDD on PPARγ1 expression in C3H10T1/2 cells [142].…”
Section: Dioxinmentioning
confidence: 99%
“…The cells were then cultured for 2 days in DMEM containing 10 µg/mL insulin and 10% (v/v) FBS. Finally, they were maintained for an additional 2 days in DMEM containing only 10% (v/v) FBS [23].…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…Cell viability in ABF ® was measured using the EZ-CYTOX kit (Daeil Lab Service Co., Seoul, South Korea), according to the manufacturer's instructions [23,24]. 3T3-L1 cells were seeded in 24-well plates at a density of 2 × 10 4 cells/well.…”
Section: Determination Of Cell Viabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, GA exhibits an endothelial protective effect, protecting the endothelium from advanced glycation end-product-induced damage by inhibiting the receptor for advanced glycation end-products/NF-κB pathway, and is thought to be important in the prevention and treatment of diabetic vascular complications [ 18 ]. Some compounds isolated from licorice exhibited peroxisome proliferator-activated receptor gamma (PPARγ) ligand-binding activity, decreased adipocyte size, and increased PPARγ mRNA expression levels in white adipose tissue [ 19 , 20 ]. Studies have demonstrated the antitumor activity of licorice; in particular, glycyrrhizin induces the apoptosis of cancer cells through caspase- and mitochondria-dependent pathways [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%